Mobile learning feasibility study towards FSKM student / Emelia Britin - Britin, Emelia (2009)
This study describes several usability criteria on m-learning which can be applied and adapted for m-learning system in the future for education. This study also measured the perception of Faculty of Computer and Mathematical Sciences (FSKM), Universiti Teknologi MARA(UiTM) student in adopting m-learning as their learning method. Here, the hypotheses have been developed in order to measure student's perception on m-learning. The objectives of the research are; to identify the usability of m-learning, to identify the FSKM student's perception in adopting m-learning as learning method and to identify m-learning features that appeal to FSKM students. To achieve the objectives in this study, data gathering method and questionnaire distribution has been used. 100 respondents participated in this study. The result have been analysed based on descriptive study, Cronbach's Alpha Reliability Test and Pearson's Correlation. Asa result from data gathering, several usability of m-learning have been identified and from the questionnaire, the hypotheses that have been developed have positive relationship between each other and also several m-learning features are identified.